Sex determination of white-tailed-deer (Odocoileus virginianus) from plasma and serum samples by using Raman spectroscopy and PLS-DA method: a forensic perspective - Majumder, Md Salahuddin; Smith, Ernest; Halámková, Lenka (Frontiers in Analytical Science, 2026)
IntroductionSpecies identification and sex determination have significant relevance in wildlife monitoring, conservation, and forensic investigations. This study explores the feasibility of using Raman spectroscopy coupled with Partial Least Squares Discriminant Analysis (PLS-DA) for sex determination of white-tailed deer (Odocoileus virginianus) based on serum and plasma samples.MethodsA total of 720 Raman spectra (360 serum, 360 plasma) were acquired from five male and five female deer. PLS-DA models were developed using full data and four calibration-to-validation splits (1:4, 2:3, 3:2, 4:1). ResultsThe serum-based PLS-DA model achieved predictive accuracies of 79.2% (1:4), 99.1% (2:3), 99.3% (3:2), and 98.6% (4:1), with balanced calibration-to-validation splits (≥2:3) demonstrating excellent robustness and generalizability exceeding 98%. The plasma-based model showed high internal accuracy (∼99.2%) but reduced external accuracy depending on the split: 85.8% (1:4), 82.4% (2:3), 86.1% (3:2), and 57.0% (4:1), reflecting greater variability and susceptibility to overfitting. Spectral comparison revealed consistent Raman bands in both matrices associated with proteins, lipids, and carbohydrates, with subtle but distinct sex-specific intensity differences. Males showed enhanced signals at ∼1,315 and ∼1,445 cm-1 (lipid regions), while females displayed stronger signals at ∼1,220 -1,280 and ∼1,540 -1,630 cm-1 (protein regions). ConclusionThese findings highlight the potential of Raman-PLSDA models —particularly with serum —as a reliable, rapid, and nondestructive method for sex classification in forensic wildlife contexts, especially when morphological features are absent or degraded. This approach may enable field-adaptable identification that enhance species conservation and forensic investigations involving incomplete or decomposed biological remains.